تأثير المستخلص المائي لأوراق اكليل الجبل في بعض وظائف الكبد في الأرانب بعد المعاملة بالأسيتامينوفين - فاضل, هيام; دريوس, محمد; شحادة, كوكب (Latakia University Journal -Biological Sciences Series, 2016)
هدفت الدراسة الحالية إلى التحقق من تأثير المستخلص المائي لأوراق اكليل الجبل في بعض التغيرات الأنزيمية للكبد بعد معاملته بجرعة من الأسيتامينوفين . قسمت الحيوانات بصورة عشوائية إلى مجموعتين ، جرّعت المجموعة الأولى بالمحلول الفيزيولوجي 0.9% طيلة مدة التجربة واعتبرت كمجموعة شاهدة ، بينما جرعت الثانية بجرعة من عقار الأسيتامينوفين مقدارها 200 ملغ/ كغ من وزن الجسم لمدة أسبوعين ، ثم أعطيت المجموعة نفسها جرعة من المستخلص المائي لأوراق اكليل الجبل مقدارها 200 ملغ/ كغ من وزن الجسم لأسبوعين تاليين .بينت النتائج أن هناك ارتفاعاً معنوياً (p<0.05) في تركيز أنزيم ALTوصبغة البيليروبين، ولم تظهر أية فروق معنوية ذات دلالة احصائية في تركيز البروتين الكلي وذلك في المجموعة المعاملة بالأسيتامينوفين، موازنة بالمجموعة الشاهدة . بينما أظهرت النتائج بعد معالجة المجموعة الثانية بالمستخلص المائي لاكليل الجبل انخفاضاً معنوياً (p<0.05) لأنزيم ALT وصبغة البيليروبين مع تسجيلارتفاعمعنويللبروتين الكلي في المجموعة نفسها موازنة بالمجموعة الشاهدة .تشير النتائج إلى أهمية نبات اكليل الجبل للكبد في التخلص من الآثار السلبية لعقار الأسيتامينوفين ، مما يشجع الإستفادة الطبية من أوراقه والمواد الفعالة المستخلصة منها .The current study was aimed to study the effect of aqueous extract of rosemary leaves in some enzymatic changes of the liver after treatment it with anintake of acetaminophen. The animals were divided randomly into two groups; The intake of first group was from physiological saline with amount of 0.9% during the period of the experiment and it was considered as a control group, while the intake of the second group was from acetaminophen drug with amount of 200 mg / kg of body weight for two weeks, then the same group was given an intake of aqueous extract of rosemary leaves with amount of 200 mg / kg of body weight for two weeks subsequent deadly.The results show that there was significantly increase (p <0.05) in the concentration of the ALT enzyme and bilirubin pigment, and it doesn't show any significant differences with significant statistically on total protein concentration and that appears in acetaminophen treatment Group, balancing the control group. While the results show after the second treatment group with aqueous extract rosemary to a significant decrease (p <0.05) of the enzyme (ALT) and bilirubin pigment with recording moral increase of total protein in the same group balancing the control one.The results indicate the importance of rosemary plant to the liver in order to get rid of the negative effects of acetaminophen drug, and that encourages the medical benefit from its leaves and its active derived substances.